FREEDOM OF INFORMATION IN ALBANIA, CONSTITUTIONAL REGULATION AND MECHANISMS TO PROTECT IT - Baraku, Irma (European Scientific Journal, ESJ, 2014)
European integration of Albania among others requests the creation and implementation of higher standards of state governing and administrating. These standards set for the first time as fundamental human right, the freedom of information and access on government documents. Setting the freedom of information asks for the just constitutional and law regulation. The article’s structure aims to put that, the first step to ensure the protection to right of information is the Constitution of the Repobblic of Albania. It provides, through its provisions, the accent on the freedom for information as a possibility of the public to fulfill their individual requests also as a possibility that is given to the administration to realise the requests of a democratic society for a governing closer to the citizens. Also, it is an important step the constitutional provision of the restriction of the right to information and the provision of the mechanisms that enable its effective protection.